Perancangan Sistem Informasi Geografis Pemetaan Penginapan PT. Kirana Bali Wisata Berbasis Web - Siahaan, William Abram Hatigoran; Rusdi, Zyad; Lewenusa, Irvan (Syntax Literate, 2023)
Tourism is an activity for someone who wants to take a vacation or travel to a place within a certain period of time and return to the place of origin with the aim of taking a short break from daily activities. Tourism has become one of the most important economic sectors in many tourist destinations around the world, including Kuta. Kuta is a tourist area located on the island of Bali, Indonesia. Kuta has become one of the most popular tourism destinations in Bali, as well as one of the most famous tourist destinations in all of Indonesia. Kuta has many attractions such as beautiful beaches, quite active nightlife, and various culinary. However, the rapid growth of tourism also brings a number of challenges that must be faced. Therefore, the creation of a Geographic Information System (GIS) as a web-based tourism mapping tool becomes relevant. With so many culinary spread in Kuta, tourists who cannot eat pigs are very difficult to find food that does not use pork content. Because, in Kuta there are so many foods that contain pork. Therefore, with the creation of this application, tourists do not need to worry because this application can provide input on culinary places that do not contain pork. To develop this GIS research using the SDLC method which includes planning, analysis, design, and implementation.